2015
DOI: 10.1111/epi.12938
|View full text |Cite
|
Sign up to set email alerts
|

Parental education predicts change in intelligence quotient after childhood epilepsy surgery

Abstract: SUMMARYObjective: To know whether change in the intelligence quotient (IQ) of children who undergo epilepsy surgery is associated with the educational level of their parents. Methods: Retrospective analysis of data obtained from a cohort of children who underwent epilepsy surgery between January 1996 and September 2010. We performed simple and multiple regression analyses to identify predictors associated with IQ change after surgery. In addition to parental education, six variables previously demonstrated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 26 publications
1
27
0
1
Order By: Relevance
“…Although this association was significant, the effect was small. In the same study, there was no relation between parental education and presurgical IQ [16]. A large twin study in a healthy British population showed the effect of genetics on intelligence to be similar among low and high socioeconomic status families [42].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although this association was significant, the effect was small. In the same study, there was no relation between parental education and presurgical IQ [16]. A large twin study in a healthy British population showed the effect of genetics on intelligence to be similar among low and high socioeconomic status families [42].…”
Section: Discussionmentioning
confidence: 85%
“…In general, postoperative cognitive outcome has been shown to correlate with seizure freedom [6,11,[13][14][15], parental education [16], antiepileptic drug (AED) policies [15,17], preoperative seizure frequency [5], and with etiology [17,18]. Importantly, earlier onset [5,9,[19][20][21][22][23][24][25][26] and longer duration [5,27] of epilepsy predict more severe cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up after surgery also varied widely, some studies reporting intervals of 4 to 11 years 19,20,22,23 or 0.9 to 15 years, 24 whereas others used fixed intervals of, for example, 2 years. [25][26][27][28] The major aim of most studies was to detect the impact, if any, of epilepsy-related variables on the cognitive outcome measures.…”
Section: Questionsmentioning
confidence: 99%
“…Presumably, parental level of education can impact outcome, as more educated parents may know better ways to enrich their children's environment. 16 According to Meekes et al 27 , parental education had a significant effect on postsurgical change in IQ, rather than on either pre-or postsurgical IQ per se. Puka et al 18 found no correlation with IQ; however, nor of other environmental variables, such as family income and residence location.…”
Section: Relationships With Environmental Influencesmentioning
confidence: 99%
“…Um estudo pesquisou o impacto do nível acadêmico dos pais sobre o crescimento nas médias de QI de crianças que foram submetidas à cirurgia para epilepsia. Os resultados demonstraram que se apenas um dos pais atingiu o nível de mestrado, isso causa um impacto de oito pontos a mais no índice de QI do filho (Meekes, Schooneveld, Braams, Jennekens-Schinkel, Rijen, Hendriks, Braun, & Nieuwenhuizen, 2015).…”
Section: Tabelaunclassified